Dural tear with multiple nerve root entrapment simultaneously after unstable spine injury: Intraoperative finding - Farid Yudoyono; Arief Pebrianto (Neurologico Spinale Medico Chirurgico, 2021)
Spinal cord injuries (SCIs) caused by trauma that frequently occur are dural tears and cerebrospinal fluid (CSF) leaks. They are not always detected with neuroimaging. Hence, the authors reported two cases of the dural tear with multiple nerve root entrapment after spine injury and described how managed. This case report was about two patients who had unstable spinal fractures. All patients have an asymmetrical neurological deficit. The following magnetic resonance imaging features have analyzed the presence of CSF leakage, epidural haematoma, and spine fractures. Both cases revealed intraoperative finding dural tear with multiple nerve root entrapment. We performed decompression with spinal fixation with a posterior approach, and then the patients were sent home without complication. During the follow-up period, none of the patients developed complications. The severe neurological deficit, fracture of laminar, and ligamentum flavum disruption on the MRI in patients were predictable factors in our cases.